Effect of Rock Phosphate along with Organic Manures on Soil Properties, Yield and Nutrient Uptake by Wheat and Chickpea - and A.B. Gosavi, A.N. Deshpande, S.S. Dalavi, S.H. Pandey, V.P. Bhalerao (Journal of the Indian Society of Soil Science, 2015)
Two separate field experiments were conducted at Post Graduate Institute, Mahatma Phule Agricultural University, Rahuri, Maharashtra on wheat and chickpea crops to test the effect of rock phosphate (RP) along with organic manures on an Inceptisols (Vertic Haplustepts) with ten treatments viz. absolute control, P control (recommended dose of N and K excluding P), recommended dose of N and K along with RP, RP+ phosphorus solubilizing bacteria (PSB), RP+pressmud cake+PSB, RP+FYM+PSB, RP+vermicompost + PSB, RP+fresh cow dung+PSB, RP+post biomethanated spentwash+PSB and single superphosphate (SSP). The incubation of RP in organic manures and PSB proved better for increasing the availability of major nutrients for both crops. Availability of P at 90 days after sowing and at harvest was significantly increased by incorporation of RP incubated with fresh cow dung and PSB. The nutrient uptake by both crops was also increased due to the application of RP with organic manures and PSB. This improvement in availability of nutrients ultimately resulted in significant increase in yield of both the crops over absolute control, P control and RP treatments. Among the organic manure treatments the availability of N and P and yield of both crops was highest in RP+fresh cow dung+PSB treatment.